Cesium heteropolyacid salts, Niobium, and Dysprosium compounds as solid catalysts in oxidation reactions of terpenic alcohols with Hydrogen peroxide and furfural acetalization. - Batalha, Daniel Carreira (2021)
Catalysis is an area of science whose advances brings important throughput in industrial processes, because simplify conditions of operation, reduces energy consumption, improves the yield of target products, and minimize environmental impact. Particularly, when renewable raw materials are involved, a catalyst can play a key role. On this sense, the development of catalysts for converting renewable origin substrates to fine chemical using environmentally benign oxidants such as H 2 O 2 has attracted interest due to environmental and economic reasons. Also, solid heterogeneous catalysts are easily recoverable and reusable at the end of the processes, reducing their cost and environmental impacts. In this work, four classes of solid catalysts were synthesized and evaluated: Cesium heteropolyacid salts (HPAs) with lacunar anions, Niobium oxides, Dysprosium-doped Zinc tungstate, and Niobium compounds treated and non-treated with Hydrogen peroxide. Synthesis methodologies for the four types of catalysts were established: precipitation processes to synthesize the HPA salts, microwave-assisted hydrothermal method to obtain the Niobium oxides that were used in the oxidation processes, coprecipitation method followed by microwave hydrothermal heating to produce the Zinc tungstate and finally, a treatment with Hydrogen peroxide of the commercial samples of Niobium compounds. These catalysts were evaluated in oxidation reactions of terpene alcohols with H 2 O 2 , a non-polluting oxidant that have only water as byproduct. Besides that, the commercial Nb catalysts were also evaluated in the furfural acetalization reactions. The catalysts were characterized by porosimetry analysis, determination of the strength and quantity of acid sites, infrared and Raman spectroscopies, powder X-rays diffraction, X-ray fluorescence analysis, thermogravimetry analysis, and electronic scanning and transmission microscopies. The effects of the main reaction parameters were assessed such as temperature, type of substrate, amount of oxidant, catalyst load, and reaction time. A review was published highlighting the properties and applicability of Niobium solids in esterification and transesterification reactions and another one is in preparation standing out the use of Niobium catalysts in different reactions.Keywords: Heterogeneous catalysts. Nerol oxidation. Cesium salts. Niobium catalysts. Hydrogen peroxide. Furfural acetalization.